Oil as an Enabler for Efficient Materials Removal in Three-Dimensional Scanning Probe Microscopy Applications - Noël, Céline; Wouters, Lennaert; Paredis, Kristof; Celano, Umberto; Hantschel, Thomas (Frontiers in Mechanical Engineering, 2021)
The ever-increasing complexity of semiconductor devices requires innovative three-dimensional materials characterization techniques for confined volumes. Multiple atomic force microscopy (AFM)-based methodologies, using a slice-and-measure approach have been proposed to meet this demand. They consist of scanning AFM probes that locally scratch away the sample’s material at a relatively high load while sensing with the secondary AFM channel, thus accessing in-depth information compared to the standard surface-limited analysis. Nonetheless, the rapid tip apex wear caused by the high forces involved, and the debris accumulation at the tip apex and inside/around the scan area, have been identified as major limitations to the accuracy and repeatability of the existing tomographic AFM sensing methods. Here we explore the use of oil as a suitable medium to overcome some of the issues such as the scan debris accumulation and the removal variability when working in air. We show how the use of oil preserves the tomographic operation while improving the efficiency in material removal for large depth sensing at a reduced debris accumulation. This is reported by comparing the results between air and oil environments, where the removal rate, depth accuracy, and tip-contamination are benchmarked. Finally, we provide the first demonstration of electrical AFM sensing using scanning spreading resistance microscopy (SSRM) in oil.